Dual anticancer activity of Aspergillus nidulans pigment and Ionizing γ-Radiation on human larynx carcinoma cell line - Hanaa Y. Ahmed; Eman M. El Gazzar; Nesreen Safwat; Monda M. M. Badawy (BMC, 2023)
Abstract Background Fungi are a readily available source of naturally generated colored compounds. These compounds might be used as radiosensitizers for treating cancer cells. Methods Aspergillus nidulans was examined for its color-producing ability in Potato dextrose agar (PDA) broth medium. The pigment was characterized by Ultraviolet (UV) spectrophotometer and Gas Chromatography Mass Spectrometry (GC/MS). Pigment extracts from A. nidulans were studied for their cytotoxic effects on the growth of human larynx carcinoma cell line (HEp-2) with or without exposure to γ-radiation at three different doses (5, 10, and 15 Gy). A. nidulans pigment cytotoxic activity was tested against normal Vero cells. Cell apoptosis was studied using flow cytometry. Gene expression of P53, Caspase 3 and Bcl-2 were quantified. Results Ultraviolet spectrum and GC/MS revealed the ability of Aspergillus nidulans to produce Rhodopin pigment. HEp-2 cells treated with A. nidulans pigment only give IC50 about 208 µg/ml. In contrast, when treated with the pigment +10 Gy γ-radiation, it give about 115 µg/ml. However, for normal cells, lower cytotoxic activity was detected. Treatment with pigment (208 g/mL) caused about 50% ± 1.0 total apoptosis level and gene expression of P53: 2.3 fold and Caspase 3: 1.84 fold in respect to untreated HEp-2), while Bcl-2 was decreased (Bcl-2: 0.63 fold in respect to untreated HEp-2). Furthermore, treated with pigment (115 µg/mL) + 10Gy caused about 47.41% ± 1.7 total apoptosis level and P53: 2.53 fold and Caspase 3: 2.0 fold in respect to untreated HEp-2, while Bcl-2 was downregulated (Bcl-2: 0.61 fold in respect to untreated HEp-2). Conclusion This study concluded that the anti-cancer activity of Aspergillus nidulans pigment was enhanced by ionizing radiation at 10 Gy, as well as its low cytotoxic activity against normal Vero cells.